2022
DOI: 10.3389/fonc.2022.854284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glycogene signature as a tool to predict the clinical outcome and immunotherapy response in breast cancer

Abstract: BackgroundBreast cancer is one of the most important diseases in women around the world. Glycosylation modification correlates with carcinogenesis and roles of glycogenes in the clinical outcome and immune microenvironment of breast cancer are unclear.MethodsA total of 1297 breast cancer and normal cases in the TCGA and GTEx databases were enrolled and the transcriptional and survival information were extracted to identify prognostic glycogenes using Univariate Cox, LASSO regression, Multivariate Cox analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Our findings indicate substantial disparities in immune cell infiltration patterns across distinct molecular subtypes of breast cancer, specifically involving B cells, T cells, and macrophages. Research has demonstrated that naive B cells are associated with a poor prognosis in breast cancer patients [ 40 ]. Moreover, higher amounts of naive B cells in the tumor microenvironment are believed to enhance metastasis and are related to tamoxifen resistance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate substantial disparities in immune cell infiltration patterns across distinct molecular subtypes of breast cancer, specifically involving B cells, T cells, and macrophages. Research has demonstrated that naive B cells are associated with a poor prognosis in breast cancer patients [ 40 ]. Moreover, higher amounts of naive B cells in the tumor microenvironment are believed to enhance metastasis and are related to tamoxifen resistance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%